The Graph of the Walras Correspondence - Balasko, Yves (Econometrica, 1975)
THE WALRAS CORRESPONDENCE associates the set equilibrium price vectors with an economy. The purpose of this paper is to study some topological properties of the graph of the Walras correspondence such as connectedness and contractibility. This is done once the graph is given the structure of a bundle. The mathematical notations used in this paper are given in Section 2. The bundle structure of the graph is proved in Section 3. The contractibility of the graph is then a straightforward result proved in Section 4. Finally, variable demand functions are introduced in Section 5 and connectivity is then proved.